2020
DOI: 10.1371/journal.pone.0224643
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptomic analysis of the response of Botrytis cinerea to wuyiencin

Abstract: Grey mould is caused by the ascomycetes Botrytis cinerea in a range of crop hosts. As a biological control agent, the nucleoside antibiotic wuyiencin has been industrially produced and widely used as an effective fungicide. To elucidate the effects of wuyiencin on the transcriptional regulation in B. cinerea, we, for the first time, report a genome-wide transcriptomic analysis of B. cinerea treated with wuyiencin. 2067 genes were differentially expressed, of them, 886 and 1181 genes were significantly upregula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…BcartB in particular, which functions in xenobiotic detoxification, increased 248-fold. This result was similar to that of Shi et al, who found that BcatrB in B. cinerea exposed to wuyiencin was upregulated 73-fold . We speculate that the increased expression of ABC transporters is a strategy of B. cinerea resistance to 2-PE.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…BcartB in particular, which functions in xenobiotic detoxification, increased 248-fold. This result was similar to that of Shi et al, who found that BcatrB in B. cinerea exposed to wuyiencin was upregulated 73-fold . We speculate that the increased expression of ABC transporters is a strategy of B. cinerea resistance to 2-PE.…”
Section: Discussionsupporting
confidence: 92%
“…The ABC superfamily and MFS superfamily are transmembrane proteins responsible for transporting myriad substrates, such as monosaccharides, oligosaccharides, amino acids, peptides, vitamins, metal ions, enzyme cofactors, drug molecules, chromophores, and nucleotide bases. , These two superfamily transporters together represent for about half of all identified genes encoding transporters in fungi; thus, they play a large role in the development, pathogenicity, and survival of fungi. Fungicides such as fenpiclonil, fludioxonil, and wuyiencin caused transcriptional modulation of ABC transporters in B. cinerea . , Specifically, the ABCG genes Bmr1 , Bmr3 , Bmr5 , and BcartB are always upregulated in fungi exposed to fungicide pressure and play roles in enhancing drug resistance. , We found that these genes were also significantly activated in B. cinerea exposed to 2-PE (Figure A and Table S3). BcartB in particular, which functions in xenobiotic detoxification, increased 248-fold.…”
Section: Discussionmentioning
confidence: 79%
“…Typically, antifungal agents for agricultural and forestry cash crops primarily act by destroying the stability of cell membranes and inhibiting the biosynthesis of proteins and nucleic acids and cell respiration. Shi et al [24] revealed the mechanisms of Botrytis cinerea controlled with the nucleoside antibiotic wuyiencin using an iTRAQ-based proteomic analysis. Based on a comparative proteomic analysis of two-dimensional (2D) gel electrophoresis, 21 differentially expressed proteins (DEPs) were identified in B. cinerea spores in response to oligochitosan, and the proteomic information combined with a biochemical analysis provided the possible mechanism by which oligochitosan inhibits fungal pathogens [25].…”
Section: Introduction Species Of Treementioning
confidence: 99%
“…Despite the widespread use of chemical fungicides to address this issue, they have inherent drawbacks, such as the development of B. cinerea resistance, environmental pollution from chemicals, and potential health hazards [11]. In contrast to chemical fungicides, microbial antagonists offer better environmental and food safety profiles while effectively controlling plant pathogens; thus, they have been employed as biocontrol agents (BCAs) worldwide for managing plant diseases [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%